Analysis of the Effect of Rail Connection Failure Using the AHP, FMECA, WRPN Methods (Case Study of the Tanjung Karang Station – Rejosari Station Crossing) - Febriyadi; Bustam, Hadyan Arifin; Setyaji, Arif; Melyta, Elyabet; Pamursari, Nurmagita; Putri, Ananda Agneshia (UNIB Press, 2025)
Rail joints are critical points in railway track infrastructure that affect passenger train ride comfort and safety. This study analyzes their impact along the Tanjung Karang – Rejosari line through Track Quality Index (TQI) and International Roughness Index (IRI Roadbump) measurements, passenger perception surveys using the Analytic Hierarchy Process (AHP), and failure risk evaluation using Failure Mode, Effects, and Criticality Analysis (FMECA) with Weighted Risk Priority Number (WRPN). Results indicate that joints with high TQI and IRI values produce significant impacts, reducing comfort. AHP identified impacts as the dominant factor, while FMECA found the highest RPN in thermite welded joints with the failure mode of “joint corrosion.” The study recommends replacing thermite welding with flash butt welding and converting mechanical joints to permanent welded joints to improve track geometry, reduce failure risk, and enhance comfort and safety.